Gardenia jasminoides Ellis: Ethnopharmacology, phytochemistry, and pharmacological and industrial applications of an important traditional Chinese medicine - Chen, Liping; Li, Maoxing; Yang, Zhiqiang; Tao, Wendi; Wang, Peng; Tian, Xiuyu; Li, Xiaolin; Wang, Weigang (Journal of ethnopharmacology, 2020)
Gardenia jasminoides Ellis is a popular shrub in the Rubiaceae family. The desiccative ripe fruits of this plant (called Zhizi in China) are well known and frequently used not only as an excellent natural colourant, but also as an important traditional medicine for the treatment of different diseases, such as reducing fire except vexed, clearing away heat evil, and cooling blood and eliminating stasis to activate blood circulation. It has also been declared as the first batch of dual-purpose plants used for food and medical functions in China. Aim of the study: This review aims to provide a critical and systematic summary of the traditional uses, ethnopharmacology, phytochemistry, pharmacology, toxicity and industrial applications of Gardenia jasminoides Ellis and briefly proposes several suggestions for future application prospects. The related information on Gardenia jasminoides Ellis was obtained from internationally recognized scientific databases through the Internet (PubMed, CNKI, Google Scholar, Baidu Scholar, Web of Science, Medline Plus, ACS, Elsevier and Flora of China) and libraries. Approximately 162 chemical compounds have been isolated and identified from this herb. Among them, iridoid glycosides and yellow pigment are generally considered the main bioactive and characteristic ingredients. Various pharmacological properties, such as a beneficial effect on the nervous, cardiovascular and digestive systems, hepatoprotective activity, antidepressant activity, and anti-inflammatory activity, were also validated in vitro and in vivo. Moreover, geniposide and genipin are the most important iridoid compounds isolated from Gardenia jasminoides Ellis, and genipin is the aglycone of geniposide. As the predominant active ingredient with a distinct pharmacological activity, genipin is also an outstanding biological crosslinking agent. Gardenia yellow pigment has also been widely used as an excellent natural dye-stuff. Hence, Gardenia jasminoides Ellis has been applied to many other fields, including the food industry, textile industry and chemical industry, in addition to its predominant medicinal uses. According to this review, Gardenia jasminoides Ellis is outstanding traditional medical plant used in medicine and food. Pharmacological investigations support the traditional use of this herb and may validate the folk medicinal use of Gardenia jasminoides Ellis to treat different diseases. Iridoid glycosides are potential medicines. Gardenia yellow pigment has been the most important source of a natural colourant for food, cloth and paint for thousands of years. This herb has made great contributions to human survival and development. Moreover, it has also achieved outstanding progress in human life and even in art. Although Gardenia jasminoides Ellis has extremely high and comprehensive utilization values, it is still far from being completely explored. Therefore, the comprehensive development of Gardenia jasminoides Ellis deserves further analysis. [Display omitted]